2017
DOI: 10.13075/ijomeh.1896.00806
|View full text |Cite
|
Sign up to set email alerts
|

Study of arsenic exposure in oral/oropharyngeal carcinoma in West Bengal

Abstract: Objectives:To study any possible correlation between arsenic toxicity and the development of oral carcinoma in West Bengal population. Material and Methods: Ethical clearance for this study was obtained from the Vivekananda Institute of Medical Sciences. Out of 30 785 patients attending our hospital from November 2012 to July 2015, 107 cases and 50 control individuals were selected. The hair and buccal smear samples were obtained upon their consent for the purpose of the analysis of arsenic count and cytogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…However, its effect in oral carcinoma is not well studied. A few studies in Taiwan, Pakistan and India have indicated its positive correlation with the occurrence of this carcinoma (Su et al, 2010, Arain et al, 2015, Pal et al, 2017, 2018. Since West Bengal is the most affected state in India, we have chosen this metal toxicity as a possible cofactor or an independent risk factor in the oral carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its effect in oral carcinoma is not well studied. A few studies in Taiwan, Pakistan and India have indicated its positive correlation with the occurrence of this carcinoma (Su et al, 2010, Arain et al, 2015, Pal et al, 2017, 2018. Since West Bengal is the most affected state in India, we have chosen this metal toxicity as a possible cofactor or an independent risk factor in the oral carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…These two areas are the worst affected areas in the world (Ratnaike, 2003). It has also been reported that arsenic toxicity may lead to the occurrence of oral carcinoma in various places (Su et al, 2010, Arain et al, 2015, Pal et al, 2017, 2018 apart from skin, lung and bladder carcinoma. So, our aim of this study is to find out whether the effect of addictions or the metal toxicity through drinking water intake is acting as the most potent factor in the development of oral carcinoma and correlate these three; selecting the population of West Bengal, India.…”
Section: Introductionmentioning
confidence: 99%
“…Aus arbeitsmedizinischer Sicht gelten UV-Strahlung, Schwefeldioxid, Asbest, Arsen Pestizide, Aerosole von starken anorganischen Säuren und brennendem Erdöl als Risikofaktoren, die zur Entstehung von Mundhöhlenkarzinomen beitragen können [8,47]. Die Exposition gegenüber Gummiprodukten, Metall-und Holzstäuben kann die Entwicklung eines Speicheldrüsenkarzinoms begünstigen [8,48,49].…”
Section: Mundhöhlenkarzinomeunclassified
“…Despite the well-documented effect of arsenic exposure in the development of skin, lung and bladder cancer, evidence of a relationship with OC is scarce. [6][7][8] OC presents precursor lesions that are not considered neoplasms, although they are related to a higher probability of developing into OSCC, known as potentially malignant lesions (PML). Those are: oral submucous fibrosis, erythroplakia, leukoplakia, chronic candidiasis, congenital dyskeratosis, lichen planus and actinic cheilitis.…”
Section: Introductionmentioning
confidence: 99%